Consumer Behavior and Purchasing Decisions toward Native Chicken in Sakon Nakhon Province, Thailand - Lertjunthuk, Laddawan; Srilapat, Chanoknan; Sriwaranun, Yaowarat; Rapankum, Narawut; Konkan, Thanada; Hanmontree, Rueangrit (Universitas Muhammadiyah Yogyakarta, 2025)
Chicken meat is an important food commodity, and growing consumer attention to food safety, nutrition, and product quality has increased interest in native chicken markets in Thailand. The study also provided information on the purchasing behavior of native chicken consumers. A multi-stage sampling method was employed to determine the 400 native chicken consumers. The primary data were collected using a structured questionnaire, and a binary logistic regression analysis was employed to identify the factors that affect consumers' decisions to purchase native chickens. The findings revealed that consumers preferred to buy whole-dressed native chicken 4 to 5 times a month, spending less than 272.46 USD. The binary logistic regression results showed that motivation, perception, price, and place significantly influenced consumers' decisions to purchase native chickens. Farmers and marketers should emphasize creating incentives and raising awareness among consumers about the quality, taste, and nutritional value of native chicken to encourage more purchases. These findings offer practical insights into native chicken consumer behavior and decision-making, with implications for expanding local and global native chicken markets.